Ada Apa dengan Kualitas Audit dalam Menggunakan Teknologi Informasi di Indonesia? - Nabila Fildzah Syakirah Sabriady; Nurul Arida Syuhada; Andi Shahrani Awalya (Academic Bright Collaboration, 2023)
This study explores the impact of information technology use on audit quality in Indonesia using the meta synthesis method. The results show that technology adoption, especially e-Audit System, has an important role in determining audit quality. The findings also highlight the importance of auditor competence in managing information technology and responding to changes in the business environment. Factors such as time pressure, objectivity, and auditor integrity also affect audit quality. This research provides a comprehensive view of the complex relationship between information technology and audit quality, making important contributions to the development of audit practices and adaptation to technology. The implications can assist audit practitioners, regulators, and stakeholders in improving the utilization of information technology for better audit quality in the future.